Impact of late effects after treatment for bladder cancer with radical cystectomy on Quality of life: a case-control study - Rikke V. Milling; Ninna K. Nielsen; Charlotte Graugaard-Jensen; Peter Christensen; Helle Pappot; Jørgen B. Jensen (Acta Oncologica)
Background and purpose: The gold standard when treating muscle-invasive bladder cancer (MIBC) is radical cystectomy (RC), a procedure that holds the potential to affect the function of several pelvic organs, causing an impact on the patient’s Quality of Life (QoL). Knowledge of the late effects following bladder cancer and treatment with RC is sparse. The aim is to describe the incidence of late effects and to investigate the impact on QoL.